2014
DOI: 10.1103/physrevlett.113.263903
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Optical Fields Through Heavily Scattering Media

Abstract: Coherent imaging and communication through or within heavily scattering random media has been considered impossible due to the randomization of the information contained in the scattered electromagnetic field. We report a remarkable result based on speckle correlations over incident field position that demonstrates that the field incident on a heavily scattering random medium can be obtained using a method that is not restricted to weak scatter and is, in principle, independent of the thickness of the scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…Acquiring a sequence of speckle measurements may also help compute an image of such an embedded moving object, as recently considered in ref. 93.…”
Section: Wavefront Shaping With Conjugation Guidestarsmentioning
confidence: 99%
“…Acquiring a sequence of speckle measurements may also help compute an image of such an embedded moving object, as recently considered in ref. 93.…”
Section: Wavefront Shaping With Conjugation Guidestarsmentioning
confidence: 99%
“…Field incident on a 9 mm thick scattering sample having µ ′ s = 4 cm −1 : (a) reconstruction from measured intensity data and (b) estimated for two apertures of 0.8 mm diameter separated by 1.6 mm, center to center. 5 Phase retrieval 8 is needed to obtain the phase term, φ(∆r), in Eq. (4), to obtain the magnitude of the Fourier spectrum of the object image.…”
Section: Aperturementioning
confidence: 99%
“…We describe an approach to access complex field information related to the object from speckle spatial correlation measurements, which are taken as the object is translated to different positions. 4,5 It is demonstrated that, after phase retrieval, imaging through or inside a strongly scattering environment is effective. This work stems from earlier understanding 6 with two beams incident on a randomly scattering medium.…”
Section: Introductionmentioning
confidence: 99%
“…light scattering | imaging | nanoparticles | plasmonics | metamaterials O ur understanding of light scattering in complex media is built almost exclusively on the interaction of light with broadband low-loss scatterers, characteristic of many natural systems such as animal tissue, fog, or sea spray (1)(2)(3)(4)(5)(6). In contrast, metallic nanoparticles possess plasmon resonances with strongly frequency-dependent absorption and scattering cross-sections, where the resonant frequency is controlled by nanoparticle size, shape, and local dielectric environment (7)(8)(9).…”
mentioning
confidence: 99%